Adsorpsi Pospat (PO4-3) Limbah Cair Laundry (Artificial) Menggunakan Arang Aktif Dari Tongkol Jagung Dengan Variasi Massa Arang Aktif Dan Temperatur Adsorpsi - Arianty Septia Ningsih; Syamsu Herman; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of laundry services has an impact on the volume of wastewater from laundry activities which has also increased. Disposal of laundry waste containing phosphate is 9.9 ppm while the limit on water emissions is 1 ppm so that the presence of excessive phosphate in the laundry liquid waste causes eutrophication. On the other hand, corn cobs waste is agricultural waste that can be processed into activated charcoal which is then applied as an adsorbent. Therefore, this study aims to find a solution to the two problems above by making the corncob as an adsorbent material for handling phosphate waste. This study shows the effect of activated charcoal mass from corn cobs waste on phosphate adsorption in laundry liquid waste and the effect of stirring temperature on the phosphate adsorption process of laundry liquid using activated charcoal from corn cobs waste as an adsorbent. The first determines the equilibrium time by means of 2 grams of activated charcoal put into a beaker glass with a Na3PO4 (500 ml) solution at a speed of 100 rpm. After the time is obtained, the equilibrium is only made for another variable. From this study, it was found that the active charcoal mass of corn cobs which best absorb Pospat solution was 3 grams and the best temperature at 50oC with adsorption efficiency of 63.30%.Keywords: activated charcoal, adsorbent, waste, phosphate, corn cobs